2011
DOI: 10.1007/s11916-011-0230-2
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Insights into Painful Diabetic Neuropathy and Treatment with Spinal Cord Stimulation

Abstract: A substantial body of literature is available on the natural history of diabetes, but much less is understood of the natural history of painful diabetic peripheral neuropathy (PDPN), a pervasive and costly complication of diabetes mellitus. Multiple mechanisms have been proposed, including polyol pathway activation, advanced glycosylation end-product formation, and vasculopathic changes. Nevertheless, specific treatment modalities addressing these basic issues are still lacking. The mainstay of treatment inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In summary, one systematic review , one exploratory overview , three prospective case series , and one retrospective cohort study that include a total of 40 patients treated with SCS for PDPN have been identified. The NACC believes that the available literature indicates that SCS seems to be an efficacious and feasible treatment for intractable PDPN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, one systematic review , one exploratory overview , three prospective case series , and one retrospective cohort study that include a total of 40 patients treated with SCS for PDPN have been identified. The NACC believes that the available literature indicates that SCS seems to be an efficacious and feasible treatment for intractable PDPN.…”
Section: Discussionmentioning
confidence: 99%
“…This pervasive and costly complication is present in up to 50% of all DM patients with long duration of disease . Although poor glucose control and cardiovascular risk factors have been reported to be associated with PDPN, exact etiology and pathophysiological mechanisms remain largely unknown . Nerve conduction studies and quantitative sensory testing may support the clinical diagnosis.…”
Section: Neuropathic Pain Associated With Various Diseasesmentioning
confidence: 99%
“…Diabetes can result in peripheral polyneuropathy in up to 50% of patients [25]. Up to 15% of the diabetic population develops painful peripheral neuropathic symptoms, mainly affecting the lower limbs [19,22,25]. Although new drugs targeting neuropathic pain have become available over the last decades, only about one third of the patients with painful diabetic neuropathy (PDN) obtain more than 50% pain relief with the use of medication [11].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic peripheral neuropathy is one of the most common and devastating consequences of diabetes mellitus, and occurs in individuals with both type 1 and type 2 diabetes (Duby et al, 2004, Said, 2007, Veves et al, 2008, Van Belle et al, 2011, Callaghan et al, 2012, Gan et al, 2012, McGreevy and Williams, 2012, Lee-Kubli et al, 2014). Up to 30% of patients with diabetic neuropathy experience debilitating pain that significantly affects their quality of life (Krein, 2005, Veves et al, 2008, Ziegler, 2008, Smith and Argoff, 2011).…”
Section: Introductionmentioning
confidence: 99%